2017
DOI: 10.1080/13548506.2017.1281976
|View full text |Cite
|
Sign up to set email alerts
|

Illness perception clusters and relationship quality are associated with diabetes distress in adults with Type 2 diabetes

Abstract: Illness perception clusters and relationship quality are associated with diabetes distress in adults with Type 2 diabetes Berry, E., Davies, M., & Dempster, M. (2017 General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights.Take down policy The Research Porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
5
17
1
Order By: Relevance
“…Reasons for exclusion were: (a) not peer reviewed (5 studies); (b) not in English (2 studies); (c) study analysis did not include clustering methods (38 studies); (d) variables other than illness representation subscales were used to create groups (27 studies); (e) illness representation was not measured using the subscales of the IPQ‐R (change scores 6 studies, Brief IPQ 5 studies, other measures 6 studies, 17 studies total); (f) sample population did not have a chronic disease (2 studies); and (g) outcome variables were not health‐related. A total of 12 studies met inclusion criteria (Aujla, Walker, Sprigg, & Vedhara, 2018; Berry, Davies, & Dempster, 2017; Flora, Anderson, & Brawley, 2015; Graham, Rose, Hankins, Chalder, & Weinman, 2013; Harrison et al, 2014; Hobro, Weinman, & Hankins, 2004; Hsiao, Chang, & Chen, 2012; Lin & Heidrich, 2012; Lopes et al, 2018; McCorry et al, 2013; Norton et al, 2014; Turkington, Dempster, & Maguire, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reasons for exclusion were: (a) not peer reviewed (5 studies); (b) not in English (2 studies); (c) study analysis did not include clustering methods (38 studies); (d) variables other than illness representation subscales were used to create groups (27 studies); (e) illness representation was not measured using the subscales of the IPQ‐R (change scores 6 studies, Brief IPQ 5 studies, other measures 6 studies, 17 studies total); (f) sample population did not have a chronic disease (2 studies); and (g) outcome variables were not health‐related. A total of 12 studies met inclusion criteria (Aujla, Walker, Sprigg, & Vedhara, 2018; Berry, Davies, & Dempster, 2017; Flora, Anderson, & Brawley, 2015; Graham, Rose, Hankins, Chalder, & Weinman, 2013; Harrison et al, 2014; Hobro, Weinman, & Hankins, 2004; Hsiao, Chang, & Chen, 2012; Lin & Heidrich, 2012; Lopes et al, 2018; McCorry et al, 2013; Norton et al, 2014; Turkington, Dempster, & Maguire, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The full results of the quality assessment are shown in Table S1, with summary information in the rightmost column of Table 2. Five of the 12 studies received scores denoting low quality (Berry et al, 2017; Harrison et al, 2014; Hobro et al, 2004; Lopes et al, 2018; Norton et al, 2014). The most frequent quality issues were: insufficient description of the sample population (8/12 studies), no reporting performance of a priori power analysis (10/12), no reported reliability data (7/12), and analyses that did not account for confounding variables (6/12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…How individuals, their partners and family make sense of Type 2 diabetes and the quality of their relationships are important determinants of adjustment and adaptation [1][2][3][4]. Conflicting beliefs about diabetes between a couple contribute to greater diabetes distress [1,2] and poorer self-care [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that diabetes distress has negative effects on self-care behaviour [3], disease control [4], medication adherence [5] and quality of life [6]. Diabetes distress may also influence illness perceptions negatively [7], which may lead to difficulties in managing diabetes and to poor glycaemic control [8]. In Malaysia, almost 20% of adults with Type 2 diabetes mellitus experience severe diabetes distress [9], a problem that deserves greater clinical attention [10].…”
Section: Introductionmentioning
confidence: 99%